A COMPARATIVE RESEARCH ON PARENTS' THOUGHTS ON REWARD AND PUNISHMENT IN EARLY CHILDHOOD EDUCATION (THE CASE OF TÜRKİYE AND NORTH MACEDONIA) - Rizvance Masan, Sehida; Dursun, Aysenur (International Scientific Journal Vision, 2023)
This study aims to comparatively examine parents' views on reward and punishment used in early childhood education. Qualitative research, case design is used in the study. Some of the results determined according to the research findings are as follows: Reward and punishment is a method deemed necessary by most of the parents in child education. But participants in Turkey, northern Macedonia and awards participants than in child education method considers that the penalty should not be used too. It was determined that most of the participants who participated in the study used reward and punishment in children's education. It has been suggested that this method is effective in children's behavioral acquisition.